TINJAUAN KEBUTUHAN MEDIA PEMBELAJARAN BIOLOGI DI SMA NEGERI 1 KECAMATAN PAYAKUMBUH, KENAGARIAN KOTO TANGAH SIMALANGGANG KABUPATEN 50 KOTA - Diana Zulyetty, Erlindawati, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Research on Review of Biological Learning Media Needs at SMA Negeri 1 Payakumbuh District, Kenagarian Koto Tangah Simalanggang, District 50 Cities Academic Year 2018/2019 has been conducted at SMA Negeri 1 Payakumbuh District from April 19-15 May 2018 assuming instructional media are needed in the learning process Biology. This study aims to determine the needs of instructional media by Biology teacher class XI IPA 1 Payakumbuh District 1 Public High School, Kenagarian Koto Tangah Simalanggang, District 50 Kota. This type of research is descriptive research. Data collection techniques in research are by distributing questionnaires. Questionnaires used were questionnaires in the form of check lists and multilevel scales. The informants of this study were teachers of class XI Science at SMA Negeri 1 in Payakumbuh Subdistrict, Kenagarian Koto Tangah Simalanggang which consisted of 2 teachers, namely teacher 1 was the mother of Agest Azri Lestari, S.Si and teacher 2 named Fany Novita Sari, M.Pd. Obstacles found in SMA Negeri 1 in Payakumbuh Subdistrict, Kenagarian Koto Tangah Simalanggang are 1.) variations or types of learning media in schools are still lacking so that the media used is just that. 2.) the existing learning media is less useful. 3.) the number of existing media is not proportional to the number of students. 4.) it is not yet known whether the media used in the Biology learning process is in accordance with the needs of the teacher as a facilitator and the needs of students as learning objek Keyword : Media needs,type of media